Automated Assembly Line with 2D Cartesian Robot and Conveyor Belt - Viviana Moya; María Maldonado; Juan Pablo Vásconez; Faruk Abedrabbo; David Pozo-Espin; Marcelo Moya (International Journal of Technology)
Industrial automation is constantly developing and considered critical to process optimization and efficiency. The integration of automated systems is traditionally focused on improving precision and productivity to significantly enhance assembly lines in producing general-purpose models in different materials such as polylactic acid (PLA) plastic. The models include toys, tools, complex mechanism components, and consumer or industrial products. Therefore, this study aimed to present the specifications for the design and testing of a low-cost teaching system for production lines using a 2D Cartesian robot and a conveyor belt. The purpose was to show how innovation in teaching industrial robotics could address the challenge of expensive systems. The proposed solution was to integrate a 2D Cartesian robot into a pneumatic gripper and a conveyor belt controlled by a Programmable Logic Controller (PLC) using a wireless connection and advanced electronic components to achieve efficient communication and operation. The results showed an accuracy of 100% in functional tests and the implications of the advances were to ensure considerable potential for reducing costs and improving learning in industrial and educational environments. The intention was to subsequently promote the implementation of new developments in the field of mechatronics.